Clinical gestational age assessment in newborns using the new Ballard score - Erman Erman; Wayan Retayasa; Soetjiningsih Soetjiningsih (Indonesian Pediatric Society Publishing House, 2016)
Background The new Ballard score (NBS) is presently consid- ered to be the most reliable method for estimating clinical gesta- tional age (GA) in newborn infants. Objective The aim of this study was to compare the NBS and Dubowitz/Finnstrom score against ultrasonography assessment of gestational age. Methods A cross sectional randomized study involving neonates born in Sanglah Hospital, Bali, June to August 2004 was carried out. Gestational age was estimated within the first 24 hour by ei- ther Dubowitz/Finnstrom score or NBS confirmed by USG (C- GLMP) as the gold standard. Results One hundred and fifty-five newborns were enrolled in this study. Subjects were randomly divided into two groups, the Dubowitz/Finnstrom score group (76 newborns) and NBS group (79 newborns). The mean age of mothers was 28.4 years old; mean birth weight was 3151.3 g (SD 596.3 g). The proportion of small for GA, appropriate for GA, and large for GA were 6%, 77% and 17%, respectively. Pearson correlation ( r ) between C-GLMP and Dubowitz/Finnstrom score was 0.71 (P<0.005); and with NBS was 0.79 (P<0.005) . Conclusion The strength of correlation between either NBS or Dubowitz/Finnstrom score and USG assessment of gestational age are similar